2019
DOI: 10.1038/s41598-019-40815-z
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin interacting motifs of USP37 act on the proximal Ub of a di-Ub chain to enhance catalytic efficiency

Abstract: USP37 is a deubiquitinase (DUB) with roles in the regulation of DNA damage repair and the cohesion of sister chromatids during mitosis. USP37 contains a unique insert of three ubiquitin interacting motifs (UIMs) within its catalytic DUB domain. We investigated the role of the three UIMs in the ability of USP37 to cleave di-ubiquitin chains. We found that the third UIM of USP37 recognizes the proximal ubiquitin moiety of K48 di-Ub to potentiate cleavage activity and posit that this mechanism of action may be ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 44 publications
(50 reference statements)
1
15
0
Order By: Relevance
“…To distinguish the roles of DUB3, OTUB1, USP27X, and USP37 in Snail protein stabilization, it is necessary to identify the potential deubiquitination site, although our data showed that USP37 displays a more efficient activity to Snail stabilization than that of DUB3. USP37 structurally constitutes an N-terminal PH domain, an internal linker, and a C-terminal catalytic domain (Yu, 2011;Kim et al, 2015;Manczyk et al, 2019). The catalytic DUB domain contains a unique insert of three ubiquitin-interacting motifs (UIMs) (Manczyk et al, 2019); however, the exact roles of the UIMs in these USP enzymes remain elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To distinguish the roles of DUB3, OTUB1, USP27X, and USP37 in Snail protein stabilization, it is necessary to identify the potential deubiquitination site, although our data showed that USP37 displays a more efficient activity to Snail stabilization than that of DUB3. USP37 structurally constitutes an N-terminal PH domain, an internal linker, and a C-terminal catalytic domain (Yu, 2011;Kim et al, 2015;Manczyk et al, 2019). The catalytic DUB domain contains a unique insert of three ubiquitin-interacting motifs (UIMs) (Manczyk et al, 2019); however, the exact roles of the UIMs in these USP enzymes remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…USP37 structurally constitutes an N-terminal PH domain, an internal linker, and a C-terminal catalytic domain (Yu, 2011;Kim et al, 2015;Manczyk et al, 2019). The catalytic DUB domain contains a unique insert of three ubiquitin-interacting motifs (UIMs) (Manczyk et al, 2019); however, the exact roles of the UIMs in these USP enzymes remain elusive. Recent data reported that mutations in UIM2 or UIM3 of USP37 result in reduced binding to ubiquitinated substrates (Manczyk et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the number of structurally unique protein domains required to coordinate DNA repair on chromatin, it is not surprising that many small molecule inhibitors are available that are potentially capable of disrupting the functions of these domains ( Arrowsmith and Schapira, 2019 ; Mio et al, 2019 ). Chemical or peptide based inhibitors have recently been developed to target several domains that are found within DDR proteins including tandem tudor domains ( Chang L. et al, 2021 ), PRC1 chromodomains ( Stuckey et al, 2016 ), PHD zinc fingers ( Wagner et al, 2012 ), bromodomains ( Filippakopoulos et al, 2010 ) and ubiquitin interacting motifs (UIM) ( Manczyk et al, 2019 ). In addition to their potential clinical applications, the development and availability to researchers of specific inhibitors of these repair-chromatin interactions will be advantageous for untangling and defining the specific contribution of individual contacts within these proteins and their ability to mediate DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the finger subdomain interacts with ubiquitin to facilitate its positioning in the catalytic center [ 93 ]. The hypothetical structure of USP37 comprises 979 amino acids residues, which consist of an N-terminal PH domain, central USP domain, C-terminal catalytic domain [ 94 ], and active sites at cysteine 350 (nucleophile) and histidine 906 (proton acceptor).…”
Section: The Structural Domains Of Usp37 and Their Associated Interactionsmentioning
confidence: 99%
“…A recent study by Manczyk et al revealed that the UIMs modulate USP37 cleavage specificity and efficiency [ 94 ]. Detailed mutational, biochemical, and enzymatic characterization of USP37 UIMs elucidated the role of each UIM in chain linkage cleavage specificity for all eight possible di-ubiquitin chain types.…”
Section: The Structural Domains Of Usp37 and Their Associated Interactionsmentioning
confidence: 99%